Financial Literacy Training for Educators: Improving Credit Management and Financial Well-being: English - IGN Oka Ariwangsa Ariwangsa; Kadek Wulandari Laksmi P; Komang Widhya Sedana Putra P (PT Ininnawa Paramacitra Edu, 2026)
Teacher staff development in the understanding of personal and professional financial management, especially related to the correct use of credit, is quite important. Hence, this paper discusses improvements in the level of understanding and knowledge of credit management among responsible teachers and employees at SD Kuta Badung through a program of financial education. The methodology was a mix of quantitative and qualitative research, as knowledge improvement was measured with pre-tests and post-tests, and the participant feedbacks were obtained with interviews and group discussions. High improvements in credit types, financial planning, and debt management accompanied by high satisfaction levels of participants reflected that it had helped in reducing stress levels and had enhanced the teachers' and staff members' well-being in their financial lives. This program thus implies that the incorporation of financial literacy in education will have a positive impact on how individuals manage their finances.